Fluorescence Enhancement of Fluorescent Unnatural Streptavidin by Binding of a Biotin Analogue with Spacer Tail and Its Application to Biotin Sensing. (20th March 2014) - Zhu, Xianwei; Shinohara, Hiroaki
Abstract : We designed a novel molecular biosensing system for the detection of biotin, an important vitamin by the combination of fluorescent unnatural streptavidin with a commercialized biotin-(AC5 )2 -hydrazide. A fluorescent unnatural amino acid, BODIPY-FL-aminophenylalanine (BFLAF), was position-specifically incorporated into Trp120 of streptavidin by four-base codon method. Fluorescence of the Trp120BFLAF mutant streptavidin was enhanced by the addition of biotin-(AC5 )2 -hydrazide with the concentration dependent, whereas fluorescence enhancement was not observed at all by the addition of natural biotin. It was considered that the spacer tail of biotin-(AC5 )2 -hydrazide may disturb the fluorescence quenching of the Trp120BFLAF by Trp79 and Trp108 of the neighbor subunit. Therefore, biotin sensing was carried out by the competitive binding reaction of biotin-(AC5 )2 -hydrazide and natural biotin to the fluorescent mutant streptavidin. The fluorescence intensity decreased by increasing free biotin concentration. The result suggested that molecular biosensor for small ligand could be successfully designed by the pair of fluorescent mutant binding protein and ligand analogue.